2012
DOI: 10.7860/jcdr/2012/4567.2366
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radius Fractures: Does a Radiologically Acceptable Reduction Really Change The Result?

Abstract: Introduction: Distal radius fractures are common fractures which are treated by orthopaedic surgeons. However, they are complex injuries with a variable prognosis and if they are not treated optimally, they can be associated with various complications. Methods and Materials:We studied 80 cases of closed distal radius fractures. These patients were treated and their X-rays were evaluated to determine whether the reduction was radiologically acceptable or not. These patients were then followed up at 1.5 and 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…2002, Chung et al. 2007, Ranjeet and Estrella 2012). Most studies describe the functional outcome over a 1-year period.…”
mentioning
confidence: 98%
“…2002, Chung et al. 2007, Ranjeet and Estrella 2012). Most studies describe the functional outcome over a 1-year period.…”
mentioning
confidence: 98%
“…They did not find a particular variable that was associated with either a good or a bad functional outcome. 7 Knirk and Jupiter, in a clinical study on patients with intra-articular distal radius fractures less than forty years old, found that the prevalence of osteoarthritis and a poor functional outcome at a mean of 6.7 years after the injury was higher for the fractures which healed with an incongruous radio-carpal joint, than for those which healed with a congruous joint. 5 Chung et al, in their study did not find any relationship between the potential predictors such as hand dominance, gender, AO fracture classification, radial height, radial inclination, complications, ulnar styloid fracture and ulnar variance, which were identified in the literature as the important factors which influenced the outcomes after intraarticular distal radius fracture.…”
Section: Resultsmentioning
confidence: 98%
“…However, other authors concluded that it was difficult to demonstrate conclusively that the reduction of the displaced fracture fragments reduced the rate of posttraumatic osteoarthritis and that they led to improved clinical results and also despite the progression of arthrosis, patients showed a high level of function suggesting no statistical correlation between the functional outcome and radiological parameters. 7,8 Whether or not acceptable radiological reduction leads to better clinical outcome, striving for an anatomic reduction of the articular surface is accepted as a desirable goal.…”
Section: Introductionmentioning
confidence: 99%
“…Although criteria for acceptable reduction of DRF have been suggested, 20 these have been based mostly on studies concerning younger adults. 4,8 Ranjeet and Estrella 21 highlight issues such as mid-carpal instability, ulnar impaction syndrome and osteoarthritis associated with poorly reduced DRF. There is still some disagreement over the importance of anatomical reduction following DRF in the elderly, with one study concluding that primary reduction in elderly, frail, low-demand patients was ineffective.…”
Section: Introductionmentioning
confidence: 99%